2019
DOI: 10.1007/s42773-019-00004-7
|View full text |Cite
|
Sign up to set email alerts
|

Biochar compost blends facilitate switchgrass growth in mine soils by reducing Cd and Zn bioavailability

Abstract: Biochars have the potential to reclaim mine-impacted soils; however, their variable physico-chemical properties incite speculation about their successful remediation performance. This investigation examined the capability of biochars produced from three different feedstocks along with a compost blend to improve switchgrass growth conditions in a mine-impacted soil by examining influences on soil pH, grass metal contents, and soil-extractable metal concentrations. Cadmium (Cd)-and zinc (Zn)-contaminated mine so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 66 publications
2
46
0
Order By: Relevance
“…In a previous seed germination study, we showed that the PL, 55, SS, and to a lesser extent 82, SG, and PC biochars increased pH vs. the controls across plant species depending to some extent on soil type, with the largest increase to about pH 6.7 for PL pyrolyzed at 700°C vs. 5.6 for the controls across the Coxville and Norfolk soils (Olszyk et al, 2018). A similar increase in soil pH was seen with PL biochar in research with a low pH mine soil (Novak et al, 2019). These increases in soil pH would lower the solubility of Fe, Mn, and Zn, thus decreasing their concentrations in solution (Barber, 1984).…”
Section: Discussionmentioning
confidence: 68%
“…In a previous seed germination study, we showed that the PL, 55, SS, and to a lesser extent 82, SG, and PC biochars increased pH vs. the controls across plant species depending to some extent on soil type, with the largest increase to about pH 6.7 for PL pyrolyzed at 700°C vs. 5.6 for the controls across the Coxville and Norfolk soils (Olszyk et al, 2018). A similar increase in soil pH was seen with PL biochar in research with a low pH mine soil (Novak et al, 2019). These increases in soil pH would lower the solubility of Fe, Mn, and Zn, thus decreasing their concentrations in solution (Barber, 1984).…”
Section: Discussionmentioning
confidence: 68%
“…Over shorter time scales (e.g., one to several years), biochars have been proven to improve environmental quality by sorbing heavy metals and organic contaminants (e.g., Sigua et al 2019;Cui et al 2019;Novak et al 2019a), positively affect soil water relations (e.g., Lentz et al 2019;Kammann et al 2011), reduce greenhouse gas emissions (e.g., Fuertes-MendizĂĄbal et al 2019;Borchard et al 2018;Jeffery et al 2016), and improve crop growth (e.g., Laird et al 2017;Novak et al 2016;Liu et al 2013). Although creation of biochars for the above purposes may seem simply based on feedstock selection, biochar production for environmental improvements is complex.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the results of Hartley et al [58] and Case et al [59] showed that biochar can be used in combination with Miscanthus for phytostabilization of Cd and Zn in contaminated soils. Novak et al [60] from their most recent study on using blends of compost and biochars concluded that the designer biochar is an important management component in developing successful mine site phytostabilization program.…”
Section: Discussionmentioning
confidence: 99%